Conflict Management from performing work of Teachers in Trang Province - Leekpai, Pradthana (King Prajadhipok’s Institute Journal, 2021)
This research aims to 1) study the causes of organizational conflicts among teachers in Trang Province, 2) study the methods of conflict management among teachers in Trang Province, and 3) compare the methods of conflict management classified by gender, age, monthly income and work experience. The samples consisted of 390 teachers with accidental sampling in Trang Province. The instrument used for data collection was a questionnaire. The statistics used for the analysis were frequency, percentage, mean, standard deviation, t-test and F-test. The results of the research revealed that teachers’ opinions towards organizational conflicts were rated on a scale of medium. The causes of organizational conflicts arose from individual factors, organizational conditions and interaction issues respectively. Conflict management methods among teachers in Trang Province were compromise, smoothing, confrontation, withdrawal and forcing respectively. The comparison of the methods of conflict management of teachers in Trang Province classified by gender, age, monthly income and work experience were not different.